Poly(G)7 box: a functional element of mammalian 18S rRNA involved in translation - Dahao Wei; Zhangyu Mai; Xinan Li; Tianli Yu; Jiangchao Li (RNA Biology)
In eukaryotes, the ribosomal small subunit (40S) is composed of 18S rRNA and 33 ribosomal proteins. 18S rRNA has a special secondary structure and is an indispensable part of the translation process. Herein, a special sequence located in mammalian 18S rRNA named Poly(G)7box, which is composed of seven guanines, was found. Poly(G)7 can form a special and stable secondary structure by binding to the translation elongation factor subunit eEF1D and the ribosomal protein RPL32. Poly(G)7box was transfected into cells, and the translation efficiency of cells was inhibited. We believe that Poly(G)7box is an important translation-related functional element located on mammalian 18S rRNA, meanwhile the Poly(G)7 located on mRNA 5’ and 3’ box does not affect mRNA translation.